PERCENTAGE OF VIABLE SPERMATOZOA COLLECTED FROM THE EPIDIDYMES OF DEATH LOCAL DOG - Sulabda, I Nyoman; Puja, I Ketut (Buletin Veteriner Udayana, 2012)
The purpose of this study to determine the effectof post mortem time on percentage of lifeepididymessperm from postmortem dog caudae epididymides. A total of 9 dog were usedand divided into three group. T0 was control group, T1, 3 hours postmortem and T2, 6hours postmortem. This way, samples were obtained at different times postmortem. Spermwere extracted from the caudae epididymes by means of cuts.The result showed that the percentage of life sperm were 67,16 ± 5.67(T0), 46.33 ± 5.60(T1) and 24.00 ± 4.35 respectively. We could appreciate that percentage of life wasaffected by postmortem time. There was significant decrease life sperm recovered fromepididymes postmortem (P<0.01). In conclusion, epididymes sperm from dog undergodecrease of percentage of life, but it could stay acceptable within many hours postmortem.We intepreted these data to indicate that it may still be possible to obtain viablespermatozoa many hours later.
Keywords: dog; epididymes spermatozoa; post mortem